Herat and its role in the Arab Islamic heritage (Journal of the College of Basic Education, 2023)
The city of Herat is considered one of the cities of the Khurasan region and one of the cities that Muslims conquered and illuminated it with the ray of Islam. Its features and peculiarity were that it was a shining path and its interaction was positive with the Arab Islamic state, and its great center in the Arabian Peninsula. Our study about this city in terms of the historical geography of the city of Herat in terms of its location, area, foundation, scientific and intellectual achievements, and its ancient and modern role that this city has practiced throughout the period of our research, and that is its significance. In the Arab-Islamic. Heritage